Editorial Note (American Journal of Islam and Society, 1987)
The complex and bewildering variety of issues and problems facing thepresent-day Muslims have made them singularly hard pressed to develop rationalstrategies and efficient policies. The intensity and multiplicity of demandshave increased to such an extent that in recent years efforts to Islamizeknowledge or recreate a Muslim way of life needs congruent thinking andprudent planning.In thinking about this question, at least two issues of adaptability and sustainabilitytake the front stage. Adaptability would mean that Islamic socialsciences and cultural habits should be sought out and adopted. This way wouldnot be an imposition of alien models or values, but a reversion to the Qur'anand Sunnah for knowledge and guidance. Once adopted, either from traditionalor modem Islamized social science, it ought to be maintained againstall odds.The American Journal of Islamic Social Sciences has been trying for thelast four years to initiate such changes in the social and individual behavior,and Islamize the knowledge with the assistance of the International Instituteof Islamic Thought and the Association of Muslim Social Scientists. Mypredecesssor, Sulayman Nyang, left such a strong record of service that wouldbe difficult for anyone to meet. I was conscious of this challenge when I wasasked and accepted to succeed him. I knew of course that I could always counton his support to maintain the Journal at the same standard, if not higher.This issue has three sections. Section one includes two papers on mattersconcerning the Islamic Thought. The first paper by Ahmad Zaki Hammadpresents Ghazali's approach to usul-al-Jiqh, divided into three elements: (i)ahkam, (ii) adilla (source), and (iii) mujtahid.. . .Of these three, the paperprovides broader explanation only of ahkams, leaving the other two for subsequentpresentations. The second paper by Bogdan Meckowski compares IbnKhaldun with Adam Smith, and other modern economists, giving Ibn Khaldunthe prominent place he deserves. With remarkable skill, Mieckowski establishesthat Ibn Khaldun favored laissez-faire, and opposed a socialized or monopolisticproduction. Accordq to Mieckowski, most modern economists borrow heavilyfrom Ibn Khaldun without acknowledging or crediting him in their works ...